CONFORTO AMBIENTAL NAS CONSTRUÇÕES DO MOVIMENTO MODERNO: O CASO DO SESC POMPEIA - Bruno, Marina; Saft, Juliana (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
This article presents a Scientific Initiation study focusing on thermal, acoustic and visual comfort at Sesc Pompeia, a project of the renowned architect Lina Bo Bardi located in Barra Funda, west zone of São Paulo City. Important information has been raised, through bibliographic review, design analysis, non-structured interviews and field research. The theoretical study encompassed conditioning factors for the environmental comfort, norms and regulations and the building characteristics. The research prioritized, among other aspects, architectural solutions, constructive components, orientation, shading, natural ventilation and thermal, acoustic and visual performance aiming to increase knowledge on the environmental performance of buildings with multiple and complex cultural uses of Paulista Modern Architecture.